Covering Political Islam: analyzing media discourses on Tunisia's Ennahda Movement - Landucci, Leonardo Pagano [UNESP] (2025)
The concept of Political Islam in International Relations has acquired new nuances as an outcome of the recent debate on religion’s presence in politics. Within this context, the field has sought to overcome the category’s inherent essentialism, producing discussions that still persist in arenas such as the media. This study examines how the idea of Political Islam is promoted by media outlets, often from a distorted and Orientalist perspective. As a case study, the Ennahda Movement in Tunisia is analyzed as a central actor that challenges this reductionist narrative through its conciliatory stance toward other political forces in the North African country. To achieve this, the research employs French Discourse Analysis and Constructivism to understand the media's discursive production in the post-Thawra period and in relation to the party. The approach includes an analysis of Western media outlets such as the BBC and France 24; BRICS agencies like G1 and TASS; and Gulf media outlets such as Al Jazeera English and Al Arabiya English. Overall, the dissertation aims to establish a connection between the development of Islamophobic thought, Orientalism, and essentialism that permeate the construction of the notion of Political Islam in the media.